Biocatalytic C3‐Indole Methylation—A Useful Tool for the Natural‐Product‐Inspired Stereoselective Synthesis of Pyrroloindoles. Issue 43 (17th September 2021) - Schneider, Pascal; Henßen, Birgit; Paschold, Beatrix; Chapple, Benjamin P.; Schatton, Marcel; Seebeck, Florian P.; Classen, Thomas; Pietruszka, Jörg
Abstract: Enantioselective synthesis of bioactive compounds bearing a pyrroloindole framework is often laborious. In contrast, there are several S‐adenosyl methionine (SAM)‐dependent methyl transferases known for stereo‐ and regioselective methylation at the C3 position of various indoles, directly leading to the formation of the desired pyrroloindole moiety. Herein, the SAM‐dependent methyl transferase PsmD from Streptomyces griseofuscus, a key enzyme in the biosynthesis of physostigmine, is characterized in detail. The biochemical properties of PsmD and its substrate scope were demonstrated. Preparative scale enzymatic methylation including SAM regeneration was achieved for three selected substrates after a design‐of‐experiment optimization. Abstract : Utilizing the promiscuous C3‐indole methyl transferase PsmD enabled the enantioselective synthesis of various pyrroloindolines. By additionally applying the halo methyl transferase Ct HMT not only the expensive SAM cofactor could be recycled, but also the enzymatic preparative scale transformation was achieved.